Development of Android-Based Classroom Presentation System by using Android Set?Top-Box - Oktaria, Dita; Herman Tolle; Aryo Pinandito (School of Computing, Telkom University, 2023)
The integration of multimedia technology in classroom presentations offers significant benefits in delivering material effectively to students and enhancing the presenter's credibility. Traditionally, teachers faced issues like weak laptop battery life and unavailability of chargers. An innovative solution to this problem is the use of set-top-boxes, compact internet-enabled mini-PCs designed for specific purposes. With new-generation set-top boxes based on Android, users can develop their applications, opening new possibilities in presentation delivery. One effective solution involves creating a centralized system to manage presentation files stored on a server accessible through the set-top box. Through functional and non-functional testing, the system proves to meet desired needs. Users reported high satisfaction rates of 93%, and the application's response time was less than one second, confirming the efficiency of the Android Set-top-box. This technology not only enhances lesson delivery but also efficiently addresses classroom presentation challenges in a user-friendly manner.